A novel method for fabricating continuous polymer nanofibers. (12th October 2016) - Du, Jiang; Liu, Daobin; Chen, Siqi; Wan, Decheng; Pu, Hongting
Abstract: A simple and efficient technique was developed to generate continuous polymer nanofibers by combining multilayer co-extrusion with a unique exit cutting die. This is an environment-friendly approach and is capable of converting multilayered films to fibers through a simple physical cutting process. Poly(lactic acid) (PLA) fibers with down to 50 nm width were successfully produced using this new technique. Interestingly, the obtained PLA nanofibers had single crystal structure, which previously formed only in dilute solutions. This new approach creates a highly efficient, versatile, and economic pathway for large-scale fabrication of polymer nanofibers. In principle, it is applicable to any melt-processable polymer, and the obtained nanofibers can be used in wide areas such as transparent nanosheets, membranes, filters, tissue scaffolds, etc . Graphical abstract: Highlights: A simple and efficient technique was developed to generate continuous polymer nanofibers. Poly(lactic acid) (PLA) fibers with down to 50 nm width were successfully produced. The obtained PLA nanofibers have special single crystal structure. Our method identifies the potential to fabricate transparent nanofiber sheets from any melt-processable polymer.